The Impact of Using an Augmented Reality e-Module for Introduction to Power Systems on Bachelor of Electronic Engineering Students at Universiti Tun Hussein Onn Malaysia - Azidin, Mustika Rawiah; Nurhanim Saadah Abdullah (Research and Innovation in Technical and Vocational Education and Training, 2025)
Augmented Reality (AR) is an interactive technology that overlays virtual elements onto the real environment in real time and has been recognized as a promising teaching aid in technical education. This study aimed to develop and evaluate the effectiveness of a marker-based AR Power Systems e-Module as an Instructional Teaching Aid (ABBM) for the subject of Power Systems, specifically the topic Introduction to Power Systems, at Universiti Tun Hussein Onn Malaysia. The module was developed using the Successive Approximation Method (SAM) and grounded in the behaviorist learning theory, which emphasizes reinforcement and feedback in an interactive learning environment. The study employed a quasi-experimental design involving undergraduate degree students of Electronic Engineering, with the treatment group utilizing the AR e-Module and the control group receiving conventional instruction. Research instruments included pre and post tests to assess students’ academic achievement and a questionnaire to determine their acceptance of the module in terms of design, content, and functionality. The analysis revealed no significant difference in achievement between the two groups; however, student acceptance of the AR e-Module was found to be very high. Overall, the AR e-Module demonstrates strong potential to serve as a dynamic ABBM in the digital-era TVET education landscape.